Subglacial bedforms and conditions associated with the 1991 surge of Skeidarárjökull, Iceland: - Waller, R.I.; Dijk, T. van; Knudson, O. (2008)
Much previous research at surge-type glaciers has sought to identify features diagnostic of surge-type behaviour. However, in comparatively little work have subglacial landform-sediment characteristics been used to reconstruct changing basal processes and conditions during surge events. Subglacial bedforms described in this article are associated with the 1991 surge of Skeidarárjökull, Iceland, and include a series of drumlins with superimposed flutes and basal crevasse-fill ridges. The drumlins were formed by the subglacial erosion of ice-contact fans. Sedimentary evidence indicates a shift from rigid-bed to soft-bed conditions during the surge. The presence of eroded but undeformed fan sediments suggests that they acted as a rigid bed when initially overridden. Subsequent deposition of a layer of deformation till resulted in a change to soft-bed conditions and the generation of flutes and subglacial crevasse-fill ridges. The lack of mixing between this till and the underlying stratified sediments indicates that subglacial sediment deformation was restricted to a thin layer and that its deposition resulted in a cessation of subglacial erosion. The drumlin is therefore a composite of both rigid-bed and soft-bed processes that illustrates changes in basal conditions and processes during the course of the event. The limited time frame in which the drumlin formed and the presence of kettleholes across its surface are distinctive features that may warrant further investigation in the search for features diagnostic of past surge events. © 2007 The Boreas Collegium.